Editorial - Armstrong , Anona (Journal of Law and Governance, 2015)
This year, 2015, the Journal of Business Systems, Governance and Ethics celebrates its tenth anniversary. During the past ten years it has provided an avenue for publication of the wide range of views and research that reflect an appreciation of what the term ‘governance’ entails.